Efektivitas Kebijakan Publik dalam Penegakan Hukum Lingkungan: Analisis terhadap Kasus Pembalakan Liar di Indonesia (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Illegal logging is a serious environmental problem in Indonesia due to its direct impact on forest destruction, biodiversity loss, and increased carbon emissions. The Indonesian government has established various public policies and legal instruments to address illegal logging practices, such as the Forestry Law, the licensing system, and strengthening law enforcement agencies. However, the effectiveness of these policies remains a concern, given that illegal logging cases continue to occur in various regions. This study aims to assess the effectiveness of public policies in enforcing environmental law, focusing on illegal logging cases in Indonesia. The method used in this study is a normative juridical approach by examining regulations, government policies, and secondary data from reports from relevant institutions and previous research results. Analysis shows that despite comprehensive public policy design, its implementation still faces various obstacles, such as weak oversight, poor coordination between institutions, limited human resources, and corrupt practices. Furthermore, social and economic factors in communities surrounding forests also influence the success of environmental law enforcement. Therefore, strengthening law enforcement agencies, transparency and accountability, and active community involvement in forest management are essential. With these improvements, public policy is expected to be more effective in preventing and combating illegal logging for the sake of environmental sustainability in Indonesia.